(untitled) (Research, Society and Development, 2020)
The bacteria involved in the gingival inflammatory process induce inflammatory responses characterized by the release of mediators, for example, interleukins, the cytokines involved in the course of development of periodontal disease are not yet fully established. The increase in the amount of interleukin-1beta (IL-1β) is correlated, in the periodontal lesion, with the progression from the stable lesion to the progressive lesion. The purpose of this literature review was to evaluate IL-1β and its influence on the development of periodontal disease. Initially, 860 articles from the following databases were evaluated in this literature review: Pubmed, Lilacs, Scielo, Web of Science, Embase and Cochrane. The search terms were: periodontal disease and IL-1β; periodontitis and IL-1β; oral health and IL-1β; gingivitis and IL-1β. With the adopted criteria, 28 articles were included in this literature review. The observed results showed that IL-1β is the one that most relates to the activity of the disease, since patients with periodontitis have a higher frequency of a genotype associated with increased production. These cytokines can be generated by immune cells, such as lymphocytes and monocytes in the medullary cavity or by other bone cells, particularly cells of the osteoblastic lineage. We conclude that IL-1β is directly related to the progression of periodontal disease, promoting the entry of inflammatory cells to the sites of infection and high levels of IL-1β are related to bleeding rates, probing depth and clinical level of insertion changed.